2020
DOI: 10.1007/s10311-020-01065-y
|View full text |Cite
|
Sign up to set email alerts
|

Analysis, fate and toxicity of chiral non-steroidal anti-inflammatory drugs in wastewaters and the environment: a review

Abstract: Non-steroidal anti-inflammatory drugs (NSAIDs) are found in the aquatic environment globally. Such drugs including naproxen, ibuprofen and ketoprofen are chiral molecules. Enantiomers of those drugs have identical physicochemical properties but can behave and interact differently in chiral environments due to differences in their three-dimensional shape. This results in enantiospecific differences in environmental fate and toxicity, which is often overlooked. Therefore, we review the analytical methods, occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 124 publications
0
22
0
2
Order By: Relevance
“…The concentrations of antibiotics (tetracyclines, macrolides and others) are reported at the level of a dozen µg/L (Zhi et al 2018;Gros et al 2019). Other classes of pharmaceuticals, for example, antihelminthics and NSAIDs, can also be detected in slurry and manure (Łukaszewicz et al 2016;Gros et al 2019;Petrie and Camacho-Muñoz 2020). A direct toxic effect from this level of concentration is unlikely, but a change in the bacteria community was observed after a continuous flow of livestock wastewater (Jia et al 2017).…”
Section: Wastewater From Livestockmentioning
confidence: 99%
“…The concentrations of antibiotics (tetracyclines, macrolides and others) are reported at the level of a dozen µg/L (Zhi et al 2018;Gros et al 2019). Other classes of pharmaceuticals, for example, antihelminthics and NSAIDs, can also be detected in slurry and manure (Łukaszewicz et al 2016;Gros et al 2019;Petrie and Camacho-Muñoz 2020). A direct toxic effect from this level of concentration is unlikely, but a change in the bacteria community was observed after a continuous flow of livestock wastewater (Jia et al 2017).…”
Section: Wastewater From Livestockmentioning
confidence: 99%
“…Ibuprofen was detected in the 10 wastewater samples at levels between 1.1 and 7.3 µg L −1 (Table 3). A recent review indicates the widespread presence of ibuprofen in wastewaters at µg L −1 [18]. In 2015, Caballo et al reported levels of ibuprofen between 0.63 and 0.68 µg L −1 in 3 different WWTPs in Córdoba (South of Spain) [19].…”
Section: Presence Of Pharmaceutical Residues and Metabolites In Wastewater Samplesmentioning
confidence: 99%
“…NSAIDs undergo several processes during wastewater treatment, but they are not entirely removed from water using conventional procedures [6,10]. This contributes to the occurrence of high levels of NSAIDs in aquatic environments, reaching values as high as µg/L concentration at multiple locations worldwide [6,11].…”
Section: Introductionmentioning
confidence: 99%